2022
DOI: 10.3390/diagnostics12123029
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Sonographic, and Hysteroscopic Features of Endometrial Carcinoma Diagnosed after Hysterectomy in Patients with a Preoperative Diagnosis of Atypical Hyperplasia: A Single-Center Retrospective Study

Abstract: Background: atypical endometrial hyperplasia (AEH) is a precancerous condition implying a high risk of concurrent endometrial cancer (EC), which might be occult and only diagnosed at postoperative histopathological examination after hysterectomy. Our study aimed to investigate potential differences in preoperative clinical, sonographic, and hysteroscopic characteristics in patients with AEH and postoperative diagnosis of EC. Methods: a retrospective single-center study was carried out on a case series of 80 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…However, they are different from the finding in a study conducted by Kurosawa et al [15], who concluded that no hysteroscopic feature could predict concurrent EC in patients with EAH found on biopsy specimens. Conversely, a controlled series by Pace et al [16], involving 80 women who underwent hysteroscopic biopsy with EAH, showed that hysteroscopicview correctly predicted underlying EC in 80.0% of cases and excluded it in 77.8% of women with confirmed EAH on hysterectomy pathology. These findings support our results and suggest that reviewing hysteroscopic imaging following an EB report of EAH can be valuable in excluding or, to a lesser extent, predicting an underlying EC.…”
Section: Ta B L E 1 Clinical Variable Retrieved From 69 Patients Unde...mentioning
confidence: 95%
See 1 more Smart Citation
“…However, they are different from the finding in a study conducted by Kurosawa et al [15], who concluded that no hysteroscopic feature could predict concurrent EC in patients with EAH found on biopsy specimens. Conversely, a controlled series by Pace et al [16], involving 80 women who underwent hysteroscopic biopsy with EAH, showed that hysteroscopicview correctly predicted underlying EC in 80.0% of cases and excluded it in 77.8% of women with confirmed EAH on hysterectomy pathology. These findings support our results and suggest that reviewing hysteroscopic imaging following an EB report of EAH can be valuable in excluding or, to a lesser extent, predicting an underlying EC.…”
Section: Ta B L E 1 Clinical Variable Retrieved From 69 Patients Unde...mentioning
confidence: 95%
“…However, due to the limited imaging criteria for identifying endometrial hyperplasia, hysteroscopic-view can be less accurate in confirming such a diagnosis, with sensitivities ranging from 50% to 75% [4,12]. Till now, only a few controlled trials have been conducted to explore the relationship between hysteroscopic imaging and the diagnosis of EAH [13,[15][16][17]. Thus, the present study is aimed to examine hysteroscopic images of patients with EAH and to determine the accuracy of hysteroscopic-view in predicting concurrent EC following a targeted EB reporting EAH.…”
Section: Introductionmentioning
confidence: 99%
“…Other intriguing articles in this Special Issue focus on the use of diagnostic imaging for the diagnosis of genital diseases, particularly in the early stages of cervical cancer [5] and endometrial carcinoma [6].…”
mentioning
confidence: 99%
“…In their retrospective study, Pace et al identified several ultrasonographic that, in conjunction with subjective hysteroscopic assessment by experienced clinicians, can suggest the presence of occult endometrial cancer in patients with a preoperative histologic diagnosis of atypical endometrial hyperplasia. These features include endometrial thickness, a larger diameter of the lesion, an interrupted endometrial-myometrial junction, and high vascular density on color Doppler imaging [6].…”
mentioning
confidence: 99%